1990–2041 Global burden of Burkitt lymphoma with 20 years forecast: A systematic analysis using the global burden disease of study of 2021 - Chengyun Dou; Yidan Sang; Hongbo Zhu; Chuangjie Cao (SAGE Open Medicine)
Background: To investigate the trends in Burkitt lymphoma incidence, mortality, and disability-adjusted life-years, considering sex and age, from 1990 to 2021, with a 20-year forecast. Method: Data regarding Burkitt lymphoma were extracted from the Global Burden of Disease study for the year 2021. Results: Globally, there were 19,072 incident cases of Burkitt lymphoma in 2021. Cases of Burkitt lymphoma experienced a 207% increase from 1990 to 2021. Over three decades, Burkitt lymphoma-associated deaths rose from 3843 to 6525. The global incidence rate of Burkitt lymphoma increased from 0.127 in 1990 to 0.236 in 2021 per 100,000 population. High body-mass indexes contribution to Burkitt lymphoma is evident in the disability-adjusted life-years, with the United States and the United Kingdom recording 0.06 and 0.05, respectively. Conversely, China and India demonstrated substantially lower contributions, at 0.02 and 0.005, respectively. The groups aged 0–14 and 50–74 years surpassed other age groups in both Burkitt lymphoma-associated incidence and death numbers. Moreover, males consistently had higher Burkitt lymphoma-associated mortality rates and numbers than females in all age groups. Furthermore, the estimated annual percentage changes of incidence with Burkitt lymphoma were positively correlated with sociodemographic index (Pearson r  = 0.606; p  = 0.003). The Bayesian age-period-cohort model predicts a significant increase in the age-standardized incidence rates of Burkitt lymphoma over the next 20 years. Interestingly, the age-standardized rates of death did not change dramatically from 1990 to 2021; and the trend is expected to remain relatively stable in the future 20 years. Conclusion: The burden of Burkitt lymphoma varies according to different regions and genders, and children of 0–14 years, adults of 50–74 years with Burkitt lymphoma disease as well as male patients need special attention. High body-mass index contributes significantly to Burkitt lymphoma burden in the United States and United Kingdom, but less so in China and India. Hopefully, this study will help optimize the prevention, diagnosis, treatment, and management of Burkitt lymphoma to reduce the disease burden.